Students’ Management for Developing Students' Potential and Talent Interests - Hikmah, fikatul; Zubaidah, Zubaidah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Student management is a crucial aspect in supporting the success of the educational process. The primary focus of this management lies in optimizing student administration, from planning and organizing to monitoring, to fully develop students' potential, interests, and talents. This article discusses the fundamental concepts, scope, as well as the objectives and functions of student management. The research methodology employed is a qualitative approach with a literature study from various relevant sources. The findings indicate that student management encompasses not only administrative activities but also the creation of a conducive learning environment that supports students' academic, social, and emotional growth. With the implementation of effective management practices, schools can enhance the quality of education and help students achieve their fullest potential, both as individuals and within the broader community. This article emphasizes the importance of student management in achieving higher-quality educational goals.